2015
DOI: 10.1063/1.4916978
|View full text |Cite
|
Sign up to set email alerts
|

Observation of longitudinal spin-Seebeck effect in cobalt-ferrite epitaxial thin films

Abstract: The longitudinal spin-Seebeck effect (LSSE) has been investigated in cobalt ferrite (CFO), an exceptionally hard magnetic spinel ferrite. A bilayer of a polycrystalline Pt and an epitaxially-strained CFO(110) exhibiting an in-plane uniaxial anisotropy was prepared by reactive rf sputtering technique. Thermally generated spin voltage in the CFO layer was measured via the inverse spin-Hall effect in the Pt layer. External-magnetic-field (H) dependence of the LSSE voltage (VLSSE) in the Pt/CFO(110) sample with H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…9(b). The magnon longitudinal spin Seebeck effect has also been observed in (Mn,Zn)Fe 2 O 4 [Uchida et al ., 2010c], NiFe 2 O 4 [Meier et al ., 2013a], Fe 3 O 4 [Ramos et al ., 2013; Wu et al ., 2015a], BaFe 12 O 19 [Li et al ., 2014b], CoFe 2 O 4 [Niizeki et al ., 2015] and in various garnet ferrites [Uchida et al ., 2013]. More recently it has also been shown that the longitudinal spin Seebeck effect can be observed in paramagnetic [Wu et al ., 2015b] and antiferromagnetic insulators in which some spin polarization is produced by a magnetic field [Seki et al ., 2015; Wu et al ., 2016b; Lin et al ., 2016] or by a ferromagnetic substrate [Prakash et al ., 2016].…”
Section: Spin Transport At and Through Interfacesmentioning
confidence: 99%
“…9(b). The magnon longitudinal spin Seebeck effect has also been observed in (Mn,Zn)Fe 2 O 4 [Uchida et al ., 2010c], NiFe 2 O 4 [Meier et al ., 2013a], Fe 3 O 4 [Ramos et al ., 2013; Wu et al ., 2015a], BaFe 12 O 19 [Li et al ., 2014b], CoFe 2 O 4 [Niizeki et al ., 2015] and in various garnet ferrites [Uchida et al ., 2013]. More recently it has also been shown that the longitudinal spin Seebeck effect can be observed in paramagnetic [Wu et al ., 2015b] and antiferromagnetic insulators in which some spin polarization is produced by a magnetic field [Seki et al ., 2015; Wu et al ., 2016b; Lin et al ., 2016] or by a ferromagnetic substrate [Prakash et al ., 2016].…”
Section: Spin Transport At and Through Interfacesmentioning
confidence: 99%
“…The SSE has been experimentally established and observed in ferromagnetic materials: metals [1], semiconductors [6,7], and oxides [8][9][10]. Theoretical models have also been developed [11][12][13][14][15].…”
mentioning
confidence: 99%
“…The SSE has been observed in a range of ferromagnetic materials: metals, 3 semiconductors, 9,10 and insulators. [11][12][13] Thus, the SSE has been experimentally established as a general transport phenomenon in ferromagnets. Since the discovery of the SSE, the study of the interaction among spin, charge, and heat currents has been strongly Schematic illustrations of (a) the conventional Seebeck effect and (b) the spin Seebeck effect (SSE) with the induced inverse spin Hall effect (ISHE) in a non-magnetic metal attached to a ferromagnetic or ferrimagnetic material.…”
mentioning
confidence: 99%